Gliptins and Cardiovascular Outcomes: A Comparative and Critical Analysis after TECOS. (15th November 2015) - Ghosal, Samit; Sinha, Binayak
Abstract : The issue related to macrovascular outcomes and intensive glycemic control was hotly debated after the publication of landmark trials like ACCORD, ADVANCE, and VADT. The only benefits seem to come from intervening early on in the disease process as indicated by the 10-year UKPDS follow-up. To complicate matters USFDA made it mandatory for modern drugs to conduct cardiovascular safety trials in high-risk populations after the 2008 rosiglitazone scare. This led to all the modern group of drugs designing cardiovascular safety trials (gliptins, GLP-1 agonists, and SGLT-2 inhibitors) to meet USFDA regulatory requirements. We saw publication of the first 2 randomized trials with gliptins published a year and a half back. On the face value SAVOR TIMI and EXAMINE satisfied the primary composite CV end-points. However, issues related to significant increase in heart failure and all-cause 7-day on-treatment mortality created a lot of confusion. FDA reanalysis of these data (especially SAVOR) raises a lot of doubts as far as CV safety of these groups of drugs was concerned. Hence, all eyes were on TECOS, which was published this year. We take a microscopic look at these trials trying to understand where we stand as from now on this issue.